Regularities of Structure and Phase Composition Formation of Surface Layer of Silumin Subjected to Electron-Beam Treatment; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Tkachenko A. V.; Petrikova E. A.; Ivanov Yu. F. Yuriy Fedorovich; Teresov A. D. (Discharge and Plasma-Beam Technology, 2016)
Title screen